What's new in modern C++ - Olsen, Andy (Pearson, 2024)
Learn how to get the most out of modern C++! Explore language and library enhancements available in modern C++. Learn how to get the most out of move semantics, functional programming techniques, smart pointers, and more. Understand important features such as variadic templates, universal references, concepts, and modules. What's New in Modern C++ helps you get up to speed with important techniques and features available modern C++. You will learn about movability and value references, smart pointers, functional programming, multithreading, and more. Expert author and trainer Andy Olsen will guide you through the new features and show you how to create and implement efficient, elegant, and contemporary code. Related Learning: Sign up for What's New in Modern C++ by Andy Olsen Sign up for more live training classes by Andy Olsen About the Instructor: Andy Olsen is a freelance consultant, instructor, and developer with more than 30 years of experience in IT. Andy began his professional career as a C/C++ developer and has also worked in Rust, Go, and other languages as the years passed. Andy is actively involved in a wide range of technologies including full-stack development, cloud native applications, data science, and more. Andy is passionate about technology education and runs training courses around the world across diverse market sectors. Skill Level: Intermediate Course requirement: None.
Online resource; title from title details screen (O'Reilly, viewed March 4, 2024)
Keywords: C++ (Computer program language); C++ (Langage de programmation); Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet